Knowledge of Nurses in The Respiratory Care Unit towards Transmissible Pathogenic Bacteria in Patients on Ventilators Continous Positive Airway Pressure: Pengetahuan Perawat di Unit Perawatan Pernafasan terhadap Bakteri Patogen yang Dapat Menular pada Pasien yang Menggunakan Ventilator Continous Positive Airway Pressure - Abdullah, Sajida Khamees; Hamzah, Mustafa Abdulkareem; Neamah, Ban Sabah; Jumaa, Zainalabideen Yasser (Indonesian Journal on Health Science and Medicine, 2024)
Background: A case of ventilator-associated pneumonia (VAP) occurs when a patient's infection with a lung infection was either not detected upon hospital admission or occurred within 48 hours of intubation and mechanical breathing. Mechanical Ventilation (MV) is a life-saving method by supporting the patient who is unable to oxygenate by their own. It is referring to deliver a volume of gas into a patient's lungs over long period of time to wash CO2. Control measures of Infection for MV patients should be done to prevent infection and complications. So that, A major responsibility that the nurse must focus on. Nurses play critical role in VAP prophylactic measures, so their knowledge in this subject is importance. Objectives: to identify level of knowledge of health care workers in the respiratory care unit (RCU) towards transmissible pathogenic bacteria in patients on ventilators (CPAP) in Al-Diwaniyah Teaching Hospital, Iraq. Methods: A descriptive design study was conducted at Al-Diwaniyah Teaching Hospital. Face-to-face questionnaire was used. The questionnaire consists of the following parts: demographic information (5 questions), Assessment of nurse’s knowledge towards transmissible pathogenic bacteria in patients on ventilators CPAP (20 questions). 23 nurses working in RCU was choosen, the sample was collected during the period from (April 1, 2024) to (August 1, 2024). Results: The study showed that most of nurses age group (95.7%) are between (20-29) years old while the majority of the participants are females (87%). Additionally, the results indicate that (52.2%) of the participants are Bachelor in Nursing. Regarding the years of experience in nursing the study results show that the participants had (1-5) Years of experience with (87%). Regarding to the participation in a previous course related to research topic, the results show that (82.6%) of the participants are not Participate in a previous course. The overall assessment show good assessment. In addition, it was determined that there was no statistically significant in participants knowledge with their socio-demographic data with (p > 0.05). Conclusion: The researcher concludes that the overall assessment, which represents the knowledge of nurses in the respiratory care unit (RCU) towards transmissible pathogenic bacteria in patients on ventilators (CPAP) in Al-Diwaniyah Teaching Hospital, shows a good overall assessment Highlights: Nurses play a crucial role in preventing VAP in ventilated patients. Descriptive study with a questionnaire involving 23 RCU nurses in Iraq. Nurses demonstrated good knowledge of VAP prevention and pathogenic bacteria. Keywords: knowledge, respiratory care unit , transmissible pathogenic bacteria, CPAP